2013
DOI: 10.1371/journal.pone.0066714
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component Analysis Based Feature Extraction Approach to Identify Circulating microRNA Biomarkers

Abstract: The discovery and characterization of blood-based disease biomarkers are clinically important because blood collection is easy and involves relatively little stress for the patient. However, blood generally reflects not only targeted diseases, but also the whole body status of patients. Thus, the selection of biomarkers may be difficult. In this study, we considered miRNAs as biomarker candidates for several reasons. First, since miRNAs were discovered relatively recently, they have not yet been tested extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…Mean accuracies were 0.791 and 0.815, respectively, and they were coincident with the mean accuracy (0.784) estimated using PCA-based LDA with UDB in a previous study [23] (see Table 1). Values of accuracy together with sensitivity and specificity values are also listed in Table 1.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Mean accuracies were 0.791 and 0.815, respectively, and they were coincident with the mean accuracy (0.784) estimated using PCA-based LDA with UDB in a previous study [23] (see Table 1). Values of accuracy together with sensitivity and specificity values are also listed in Table 1.…”
Section: Resultssupporting
confidence: 87%
“…PCA-based unsupervised FE was used for the previous UDB discovery [23]. The importance of stability was previously demonstrated by Wehrens et al [24], who showed that a stable FE improved the performance.…”
Section: Resultsmentioning
confidence: 99%
“…Reason for the discrepancy in separation of samples to three groups with and without normalization is unclear. However, a recent study has shown PCA as a better method to identify circulating microRNAs 18 . Samples utilized in this study were from inbred mice housed under similar condition, and collected and analyzed at the same time, which should limit inter-mice and technical variability.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the identification of individual genomic loci or genes as biomarkers from large datasets requires robust statistical testing such as multiple-testing correction (although traditional tests like the Bonferroni correction are over-conservative since there is often correlation between loci, i.e., they are not independent) or stringent false discovery rate (FDR) control (for example, by the Benjamini–Hochberg procedure) [8082]. To define sets of biomarkers from large dataset, alternative statistical methods (such as sparse principle component analysis (PCA) or sparse canonical correlation analysis (CCA) [83, 84]) are available as well. In light of (i) challenges with the experimental setup when using patient material, (ii) costs, and (iii) the extensive computational analysis associated with the exploratory phase of biomarker discovery, genome-wide screens are often performed on relatively small cohorts.…”
Section: Main Textmentioning
confidence: 99%